2023
DOI: 10.3390/tropicalmed8020085
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Mortality Rate Is Associated with Illiteracy, Age, and Air Pollution in Urban Neighborhoods: A Spatiotemporal Cross-Sectional Analysis

Abstract: There are different area-based factors affecting the COVID-19 mortality rate in urban areas. This research aims to examine COVID-19 mortality rates and their geographical association with various socioeconomic and ecological determinants in 350 of Tehran’s neighborhoods as a big city. All deaths related to COVID-19 are included from December 2019 to July 2021. Spatial techniques, such as Kulldorff's SatScan, geographically weighted regression (GWR), and multi-scale GWR (MGWR), were used to investigate the spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 102 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…The authors state that spatially correlated data are geospatial data with spatial autocorrelation and variability that originate from each region and have adjacency to another region. Mortality rates from COVID-19 and their geographical associations with various socio-economic and ecological determinants in Tehran through the use of spatial techniques apply [ 42 ]. There is also a cross-sectional study from the Iranian environment that examined spatiotemporal patterns in northeastern Iran from 2016 to 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The authors state that spatially correlated data are geospatial data with spatial autocorrelation and variability that originate from each region and have adjacency to another region. Mortality rates from COVID-19 and their geographical associations with various socio-economic and ecological determinants in Tehran through the use of spatial techniques apply [ 42 ]. There is also a cross-sectional study from the Iranian environment that examined spatiotemporal patterns in northeastern Iran from 2016 to 2020.…”
Section: Methodsmentioning
confidence: 99%
“…This article uses the multiscale geographically weighted regression method (MGWR), the extended and advanced version of GWR. This spatial regression technique explores geographically varying relationships between dependent variables and explanatory variables; MGWR is being used to analyze a variety of problems in geography, urban planning, and various other disciplines [84,85]; studies proved the reliability of MGWR in modeling the COVID-19 issues [86][87][88]. Geographically weighted regression (GWR) allows the coefficients to vary spatially, but all coefficients must change at a similar rate across the study area.…”
Section: Methodsmentioning
confidence: 99%
“…This research also showed that the female mortality rate is lower than the male mortality rate. From the age aspect, the mortality rate is 68% higher among the elderly group (those aged more than 65 years old), while the young generation (those aged 25 years old and below) has the lowest mortality rate ( Mohammadi et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%